IRAN’S GEOPOLITICS IN THE MIDST OF THE U.S.-RUSSIA-CHINA ENERGY SECURITY STRUGGLE FOR GEOSTRATEGIC CONTROL OVER EURASIA - (Thrassy) N. MARKETOS, Thrassyvoulos (CENTRAL ASIA AND THE CAUCASUS, 2009)
For reasons of both world strategy and control over natural resources, the U.S. administration is determined to secure a dominant role in Eurasia for itself. The Eastern Caspian shore of the Central Asian states of Kazakhstan and Turkmenistan is crucial to oil and gas flow control, because determining which one, or both, of the two major projects—the Trans-Caspian Corridor plus the Nabucco pipeline or the Caspian pipeline plus the South Stream pipeline—will reach the European or Asian market will in effect determine which major power, the U.S., Russia, or China, will gain geostrategic control over Eurasia.The important geographical location of Central Asia (CA) with respect to the transport and communication networks in the West-East and North-South directions, concentration of the sizable fuel reserves there, as well as its vulnerability to the problems of the neighboring regions of South Asia and the Middle East has revived the ideas of the “Heartland” and “Eurasian Balkans” with the emphasis on the specific role and significance of CA in world politics.The struggle of the leading world powers (U.S., Russia, and China) for geopolitical and geoeconomic domination in the Caspian region is explained first by their geostrategic aspirations for leadership in the post-Cold War world order, as well as by the necessity to solve various regional and global security problems, many of which are linked with the Islamic Republic of Iran.This paper argues that the key to this equation is Iran. In fact, how Moscow proceeds with the reconfiguration of Russo-Iranian relations could well form the centerpiece of the geopolitics of energy security in Eurasia. Moscow can be expected to make vigorous efforts to coordinate with Iran over its oil and gas output and exports. The rationale for such a coordinated strategy involving Iran is very obvious. First, Moscow is intensely conscious of the West’s awareness of Iran’s enormous untapped hydrocarbon reserves as an alternative to Russian supplies. Russia will strive to stay ahead of the European, and eventually American, overtures toward Iran. Second, the hydrocarbon sector in Iran is firmly under state control and Moscow and Tehran are in harmony in this regard. Third, the two countries will be coordinating their energy policies for wider geopolitical purposes within the broad framework of their strategic cooperation. Furthermore, market forces dictate the rationale of Russia-Iran cooperation. Moscow would simply like to avoid competing with Iran as a major oil and gas route connecting the Caspian and Central Asian energy-producing countries. Russia and Iran control roughly 20% of world’s oil reserves and close to half of the world’s gas reserves, and it makes good sense to accommodate each other.Iran is indeed an important energy partner for Russia for many reasons. Russian oil companies, flush with funds, are keen to invest abroad. The Iranian upstream oil and gas sector and Iran’s energy ventures, such as pipeline projects, offer an attractive proposition for Russian investment. Again, Iran’s geographical location is ideal as an export outlet for expanding Russian energy exports, especially its ambitious developing liquefied natural gas (LNG) industry. Besides, Iran is an influential member of the Organization of Petroleum Exporting Countries, the decisions of which have a bearing on price stability and Russian export volumes.